Teaching of native languages in Law Schools in a multicultural and multilingual country as Peru - Bermúdez Tapia, Manuel (2022)
Due to the lack of integration of Peru’s population for ethnic, social, demographic, and political reasons, the levels of violence and social exclusion have not been related to the need of training professionals in multicultural values. This need has only been addressed in the school context, yet the creation of bilingual and intercultural universities has also contributed positively. However, this may only lead to partial processes of development and population integration. Therefore, a proposal is made for training professionals, especially lawyers, to ensure a much more productive social integration process. Thus, the particular socio-legal contexts could be better understood, leading to a better protection of the rights of indigenous populations, especially in the judicial field.